2014
DOI: 10.1002/2014jc009994
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal to interannual variability of the Atlantic meridional overturning circulation from eddy‐resolving simulations and observations

Abstract: There is a good agreement between the model and the observation for all components of the AMOC at 26.5 N, whereas the agreement at 41 N is primarily due to the Ekman transport. We found that (1) both observations and model results exhibit higher AMOC variability on seasonal and shorter time scales than on interannual and longer time scales; (2) on intraseasonal and interannual time scales, the AMOC variability is often coherent over a wide latitudinal range, but lacks an overall consistent coherent pattern ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 77 publications
3
31
0
Order By: Relevance
“…After 3 years of data were recovered, a seasonal cycle of the MOC became apparent , with a maximum in July-November and a minimum in March, and a seasonal range of approximately ±3.5 Sv. This seasonal cycle has been captured by numerical simulations (Xu et al, 2014) and may be explained by variations in wind-forcing on seasonal timescales (Yang, 2015;Duchez et al, 2014). Kanzow et al (2010) also noted that the components of the MOC (the Florida Current, the interior thermal-wind contribution, and the Ekman flow) were largely uncorrelated, suggesting that each contributes variability to the MOC independently.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…After 3 years of data were recovered, a seasonal cycle of the MOC became apparent , with a maximum in July-November and a minimum in March, and a seasonal range of approximately ±3.5 Sv. This seasonal cycle has been captured by numerical simulations (Xu et al, 2014) and may be explained by variations in wind-forcing on seasonal timescales (Yang, 2015;Duchez et al, 2014). Kanzow et al (2010) also noted that the components of the MOC (the Florida Current, the interior thermal-wind contribution, and the Ekman flow) were largely uncorrelated, suggesting that each contributes variability to the MOC independently.…”
Section: Introductionmentioning
confidence: 78%
“…This means that excess northward flow in the boundary current is returned horizontally within the upper mid-ocean circulation rather than by deeper layers in the interior, which would have involved changes in the MOC. The region east of the Bahamas is known to be rich with eddies, which may influence the transbasin transports (Wunsch, 2008;Kanzow et al, 2009;Thomas and Zhai, 2013;Clément et al, 2014;Xu et al, 2014), and due to the timescale of observed compensation, we suspect that eddies are involved.…”
Section: Umo and Fc Transports: Horizontal Circulationmentioning
confidence: 99%
“…Results from eddy-resolving, 1 /128 Atlantic simulations with the Hybrid Coordinate Ocean Model (HYCOM; Bleck 2002;Chassignet et al 2003) have been used previously in examining the currents and transports connected with the AMOC (Xu et al 2010(Xu et al , 2012(Xu et al , 2013(Xu et al , 2014. Particularly relevant to the topic here, Xu et al (2010) considered the volume transport and u/S properties of overflow waters after they flow over the GreenlandScotland Ridge into and within the Irminger Sea.…”
Section: Model Configurationsmentioning
confidence: 99%
“…Particularly relevant to the topic here, Xu et al (2010) considered the volume transport and u/S properties of overflow waters after they flow over the GreenlandScotland Ridge into and within the Irminger Sea. The multiple ISOW pathways in the model [see Kanzow and Zenk (2014) for observational support] provide a possible explanation for the small westward transport observed in ISOW through the Charlie-Gibbs Fracture Zone (CGFZ), which is roughly 60% of deep transport upstream and downstream.…”
Section: Model Configurationsmentioning
confidence: 99%
See 1 more Smart Citation